Improving women’s dietary diversity in Kenya: Results from a cluster-randomized trial on chicken production and nutrition education - Geremew, Kumlachew; Chelangat, M.S.; Ouko, O.; Yemane, Tsion; Ouko, V.O.; Odiwour, A.; Alaru, P.A.; Mbuku, S.; Dessie, Tadelle (2025)
Background: Micronutrient deficiencies among women in low-and middle-income countries pose a significant threat to maternal and child health. Limited dietary diversity—marked by heavy reliance on staple foods and low consumption of nutrient-rich options—exacerbates these deficiencies. Objective:This cluster-randomized controlled trial evaluated whether promoting chicken production, with or without nutrition education, could improve women’s dietary diversity, as measured by the Minimum Dietary Diversity for Women (MDD-W) indicator. Methods:The trial was conducted in Kakamega and Bomet counties, Kenya, with participants randomized into three groups: (1) chicken provision only, (2) chicken provision plus nutrition education, and (3) control. Dietary diversity was assessed using the 10-food group MDD-W score. Results:At baseline, the average dietary diversity score was low (mean: 4.27 ± 1.25), and only 35% of women met the MDD-W threshold. Diets were primarily composed of cereals (21.6%), dairy (20.0%), and leafy vegetables (16.7%), with limited intake of protein-richand vitamin A-rich foods. The combined chicken and nutrition education intervention led to a significant improvement in dietary diversity in Kakamega (mean difference: 0.323; p= 0.002), but not in Bomet. Despite improvements, 62–68% of participants still failed to meet the minimum dietary diversity threshold post-intervention. Conclusion:Nutrition education enhanced the effectiveness of food-based interventions in one of the two counties. However, persistent dietary inadequacies suggest that integrated strategies combining food access, behavior change communication, and agricultural diversification are necessary to sustainably improve women’s diet quality and micronutrient intake.